CB2R Activation Regulates TFEB-Mediated Autophagy and Affects Lipid Metabolism and Inflammation of Astrocytes in POCD - Zhang, Lieliang; Wang, Xifeng; Yu, Wen; Ying, Jun; Fang, Pu; Zheng, Qingcui; Feng, Xiaojin; Hu, Jialing; Xiao, Fan; Chen, Shoulin; Wei, Gen; Lin, Yue; et al. (Frontiers in Immunology, 2022)
Several recent studies provide contemporary evidence that accumulation of lipid drots (LDs) will accelerate the damage of mitochondria and increase the release of inflammatory factors which has been implicated as a mechanism of neurodegenerative disease or tumor disease, also in aging-related diseases postoperative cognitive dysfunction (POCD). We found that activation of astrocyte and lipid accumulation in the hippocampus after surgery.However, activation of cannabinoid receptor type II (CB2R) could significantly reduce the accumulation of lipids in astrocytes and change the expression of lipid metabolism genes, at the same time reduce the release of inflammatory factors interleukin-1 Beta (IL-1β )and interleukin 6 (IL-6) in peripheral serum and improve the cognitive ability of POCD mice.In further investigation of mechanisms, we found that activation of CB2R promoted nuclear entry of the bHLH-leucine zipper transcription factor transcription factor EB (TFEB), a master transcription factor of the autophagy-lysosome pathway, and reduce the phosphorylation of TFEB-S211 at the same time. When CB2R promoted TFEB into the nucleus, TFEB bound to AGCACATGCC element in promoter region of PGC1α, promoting the transcription of PGC1α and accelerateing downstream lipid metabolism. The above process led to the activation of autophagy and decreased cellular lipid content.our research confirmed the new mechanism of CB2R in POCD regulating lipid metabolism and inflammation.